Serviceability Assessment Method of Stay Cables with Vibration Control Using First-Passage Probability. (6th May 2019) - Jeong, Seunghoo; Lee, Young-Joo; Sim, Sung-Han
Abstract : As the construction of long-span bridges such as cable-stayed bridges increases worldwide, maintaining bridge serviceability and operability has become an important issue in civil engineering. The stay cable is a principal component of cable-stayed bridges and is generally lightly damped and intrinsically vulnerable to vibration. Excessive vibrations in stay cables can potentially cause long-term fatigue accumulation and serviceability issues. Previous studies have mainly focused on the mitigation of cable vibration within an acceptable operational level, while little attention has been paid to the quantitative assessment of serviceability enhancement provided by vibration control. This study accordingly proposed and evaluated a serviceability assessment method for stay cables equipped with vibration control. Cable serviceability failure was defined according to the range of acceptable cable responses provided in most bridge design codes. The cable serviceability failure probability was then determined by means of the first-passage problem using VanMarcke's approximation. The proposed approach effectively allows the probability of serviceability failure to be calculated depending on the properties of any installed vibration control method. To demonstrate the proposed method, the stay cables of the Second Jindo Bridge in South Korea were evaluated and the analysis results accurately reflected cable behavior during a known wind event and show that the appropriate selection of vibration control method and properties can effectively reduce the probability of serviceability failure.